Legal Protection For Consumers On Withdrawal Of Fiduciary Objectives By Financing Companies Due To Covid 19 In Mataram City - Edi Yanto; Rena Aminwara; Sahrul Sahrul (Faculty of Law, University of Mataram, 2022)
The purpose of this study is to obtain the first description: legal protection for consumers for the withdrawal of fiduciary guarantee objects by finance companies due to Covid 19, and second: the role of the Mataram City Consumer Dispute Resolution Agency (BPSK) in resolving consumer financing disputes in Mataram City. This type of research is a normative and empirical law that examines legal materials and data. The approach used is legislation and concepts, then analyzed with qualitative description. Legal protection for consumers for the withdrawal of fiduciary guarantee objects by financing companies due to covid 19. The government issues a Countercyclical policy through restructuring or credit relaxation for debtors with the potential to have difficulty fulfilling their obligations; however, suppose the restructuring effort does not result in a settlement. In the case, dispute resolution is carried out based on the clauses in the agreement or credit agreement signed by the parties. The Mataram City BPSK resolving consumer financing disputes due to Covid 19 in Mataram City, has an essential role as a quasi-judicial institution in resolving consumer disputes out of court. This institution was born as a form of equitable distribution of justice for the community, especially consumers who have not had access to dispute resolution in the judiciary.